Perencanaan dan Perancangan Fasilitas Co-Housing With Nature di Denpasar: Bahasa Indonesia - I Made Windhu Langun Sastra; Ida Bagus Gede Parama Putra; I Gede Surya Darmawan; I Nyoman Nuri Arthana; Putu Gede Wahyu Satya Nugraha (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Millennials in Bali are facing difficulties in home ownership, with around 30% of the population without a place to live. To meet the need for housing that supports open social life, the development of Co-housing in Denpasar is important. Co-housing is designed to provide shared spaces that maintain the privacy of residents while facilitating social interaction. However, co-housing designs face issues such as space constraints, privacy, and cultural integration. Ensuring compliance with environmental regulations is also a challenge. The design process uses a combined approach of Research Method and Design Method, focusing on maximizing minimal space and utilizing connecting elements. The use of green concrete is expected to reduce CO2 emissions and create a comfortable environment for residents. Co-housing is expected to be a sustainable solution to Bali's housing needs.